Facile synthesis of oligo(3-hexylthiophene)s conductive wires with charge-transfer functions. Issue 17 (11th April 2017) - Öktem, Gözde; Sahre, Karin; Voit, Brigitte; Jordan, Rainer; Kiriy, Anton
Abstract : A series of fully conjugated oligo(3-hexylthiophene)s bearing different starting- and end-groups have been synthesized by means of externally initiated Kumada catalyst-transfer polymerization (KCTP) and Grignard Metathesis Polymerization (GRIM). Abstract : A series of fully conjugated oligo(3-hexylthiophene)s bearing different starting- and end-groups have been synthesized by means of externally initiated Kumada catalyst-transfer polymerization (KCTP) and Grignard Metathesis Polymerization (GRIM). These kinds of oligomers' starting- and end-groups include tert -butyl protected thiols to be used for binding of oligomers to gold electrodes and tetracyanobutadiene-based donor–acceptor (DA) end-groups, such as dimethylaniline-tetracyanobutadiene (DMA-TCBD) and ferrocene-tetracyanobutadiene (Fc-TCBD), introduced to control the charge transport through the oligomers. The DMA-TCBD and Fc-TCBD end groups were incorporated by means of a Diederich-type click transformation of appropriately end-terminated oligo(3-hexylthiophene)s. The efficiency of the end-group functionalization was comprehensively assessed by NMR spectroscopy and MALDI-TOF spectrometry whereas the redox activities of the DA end-groups were examined by cyclic voltammetry. KCTP showed a much superior performance compared to GRIM in the introduction of a desirable end-group functionality. The thus-prepared conjugated oligomers are attractive materials for application in molecular electronics which will be explored in future studies.